13C isotopomics of triacylglycerols using NMR with polarization transfer techniques1. Issue 12 (21st June 2015) - Merchak, Noelle; Bejjani, Joseph; Rizk, Toufic; Silvestre, Virginie; Remaud, Gerald S.; Akoka, Serge
<x xml:space="preserve">Abstract</x> A rapid and very precise method is proposed to simultaneously determine the position-specific 13C content and the metabolomic profile of triacylglycerols (isotopomics). Powerful origin tracers such as , , , and become rapidly available.